Asymmetric effects of monetary policy in ASEAN-4 economies - Tan, Siow Hooi; Habibullah, Muzafar Shah; Mohamed, Azali (EuroJournals Publishing, 2010)
By employing the Markov-switching model, this study examines if real output asymmetrically responds to monetary policy shocks in Indonesia, Malaysia, the Philippines and Thailand. This study provides evidence that a contractionary monetary policy has a larger absolute impact than an expansionary policy. Moreover, the effects of an expansionary policy are gradually mitigated when the inflation rate is increasing (except in Malaysia). These findings imply that monetary authorities must consider not only the behaviour of the inflation process but also the fact that not all economies can react in a similar way to expansionary and contractionary monetary policy shocks.